The best of the Laurie Berkner Band [compact disc]. (Two Tomatoes, 2010)
Laurie Berkner and her band perform frequently on Nickelodeon and were guest artists on Ziggy Marley's hit 2009 album Family Time. This greatest hits collection features all the most popular tunes from all five of Laurie Berkner's albums and other releases.